Heterotrophic ossification post total knee arthroplasty in a patient with rheumatoid arthritis: a case report - Veliyil, Aswin Thankachan; S., Dileep; Mathew, Renjit John; John, John Thayyil (International Journal of Research in Orthopaedics, 2021)
Even though minor degrees of heterotrophic ossification are common in total knee arthroplasty, it is of little clinical significance. But severe degrees of heterotrophic ossification are very rare after total knee arthroplasty. Here we discuss about a 70 years old woman who initially had excellent post-operative range of movements after cemented total knee arthroplasty, but later presented with knee pain, swelling and loss of range of movements after 3 months. X ray showed severe heterotrophic ossification around knee near the quadriceps tendon. She was treated conservatively with non-steroidal anti inflammatory drugs and physiotherapy. After a period of 3 months of physiotherapy, patient regained the lost range of movements and is currently under follow up for the past 1 year. Hence this case instantiates that even in cases of severe Heterotrophic Ossification after total knee arthroplasty, non-operative treatments such as physiotherapy with anti-inflammatory drugs should be the primary option to treat the stiffness before considering surgery.